Inuvialuit Traditional Ecological Knowledge (TEK) of Beluga Whale (Delphinapterus leucas) in a Changing Climate in Tuktoyaktuk, Northwest Territories - Pearce, Tristan; Waugh, Devin (Polar Data Catalogue, 2017)
The research was conducted with community members in Tuktoyaktuk, NWT, following established community based research methods. A pre-research consultation was conducted through a community visit and participation in the Inuvik Beluga Summit in February 2016. Data were collected with a local Inuvialuit community researcher during a field season between June and August 2016 using ethnographic field methods including semi-structured interviews and participant observation. Interviews were conducted with 17 active and formerly active harvesters, and included open ended questions and participatory mapping. The interview guide was modeled after a similar study conducted in Ulukhaktok, NWT (Pearce & Collings, in review ), and focused on knowledge of beluga behavior and ecology, hunting techniques, and subsistence food preparation.